The influence of agro-ecological factors on yield and quality of medicinal crops - Onipko, V.; Hordivska, S. (Scientific Progress & Innovations, 2023)
Medicinal plants were the oldest form of natural medicine that mankind had, and it was almost forgotten with the development of traditional medicine. However, over the past few decades, the study of natural remedies has been gaining relevance, which contributes to the development of the medicinal plant market. The purpose of the article is to analyze the impact of agroecological factors on the yield and quality of medicinal plants in Ukraine as factors of the industry development. Among the most promising and popular medicinal plants grown in Ukraine, Echinacea purpurea, mallow flower, blue cornflower and St. John's wort were considered. It has been determined that it is better to plant Echinacea purpurea in the 3rd decade of March, carry out seed stratification for 30–45 days and pre-sowing treatment with a growth stimulant. Increasing the yield of rhizomes and roots of Echinacea is possible when carrying out moldboard plowing of the soil during the main cultivation to a depth of 20–22 cm. The measures to ensure the yield and quality of mallow are considered: seed stratification for 15 days; sowing in warm and well-moistened soil at the optimal time as for late spring; joint crops with corn; fertilizing with organic and mineral fertilizers in accordance with the growing season; weed control. The agro-ecological factors of the productivity and quality of blue cornflower are revealed: good predecessors (clean or engaged fallows, grains, row crops and leguminous crops); sowing in autumn (3rd decade of October); seed stratification for 30 days; the usual row sowing method (with a row spacing of 15 cm). To produce high yields and quality of St. John's wort: the best predecessors (clean or occupied fallow land, cereal crops); for seed propagation, stratification for up to 45 days or pre-sowing irradiation of seeds is necessary; for seedling propagation, it is advisable to add peat and peat to the substrate; fertilizing with mineral and organic fertilizers according to the years of life; forming a planting density of up to 83 thousand plants/ha.